1988
DOI: 10.1111/j.1467-8624.1988.tb01471.x
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Negative Emotional States and Adjustment from Early Childhood through Adolescence

Abstract: The relations among various negative emotional and behavioral characteristics (e.g., aggression, anxiety, undercompliance, depressive mood) and adjustment were examined through use of data from the 31-year-old New York Longitudinal Study. 75 white, middle-class children were rated on these negative characteristics from infancy to adolescence. Measures of family, peer, and personal adjustment were also obtained. Because of the longitudinal nature of the data, we were able to use structural equation models to ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 8 publications
4
39
0
Order By: Relevance
“…Indeed, women often derive a sense of the positive self from their ability to enter and maintain close relationships (Kaplan 1986). Yet, they often do so by suppressing negative feelings and their own needs during social interactions (Lerner et al 1988;Piran and Cormier 2005). The emphasis here is on concealing the negative self that is perceived to be in conflict with social expectations in order to achieve relationship wellbeing.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, women often derive a sense of the positive self from their ability to enter and maintain close relationships (Kaplan 1986). Yet, they often do so by suppressing negative feelings and their own needs during social interactions (Lerner et al 1988;Piran and Cormier 2005). The emphasis here is on concealing the negative self that is perceived to be in conflict with social expectations in order to achieve relationship wellbeing.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…The literature on wellbeing, especially with reference to gender, has long emphasized the complex interplay between personal and social wellbeing (Lerner, Hertzog, Hooker, Hassibi and Thomas 1988;Piran and Cormier 2005). This is of particular relevance to women because they are often socialized into the role of a caregiver (e.g., daughter, friend, wife or mother) who puts the needs of others before their own (Jack 1991;Thompson 1996).…”
Section: Theoretical Foundationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicate that continuity in maternal distress from offspring's early to middle childhood has a strong effect on offspring's experiences of distress in adulthood-over half of the indirect effect of maternal distress at offspring's age of five on offspring's distress in adulthood occurs through mother's distress at offspring's age of 10. Given that symptoms of adult psychological distress tend to remain stable (Lerner et al 1988), children who are exposed to mothers with distress symptoms at an early age are likely to continue to be exposed to mothers with such symptoms in middle childhood. Thus, the cumulative effect of continued exposure to mothers with some level of distress has negative effects on the children's psychological well-being in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Lerner, Hertzog, and Hooker (1988) proposed that self-silencing can be viewed in the form of internalized anger, as women learn that their expressions of anger are judged by others to be inappropriate and tend to push others away. Similarly, Hooker and Convisser (1983) suggested that, in attempt to suppress their anger, women may learn to engage in bingeing or emotionbased eating, essentially swallowing their anger, which then places them at higher risk for developing an eating disorder.…”
Section: Self-silencing and Disordered Eating Attitudesmentioning
confidence: 99%